Empowerment in chronic wound care-exploring the scope for patient contribution† - Hackert Benedikt; Stürmer Ewa Klara; Weger Ulrich (Sciendo, 2024)
In this study, we investigated the concept of empowerment in chronic wound care and propose to facilitate patient control by making use of degrees of freedom (DOF): that is, shaping of everyday wound care tasks initiated by patients and based on their wishes, mostly in terms of patients executing treatment steps, requesting or directing health care professionals to undertake changes, or modifications of internal states.